Thermal-hydraulic characteristics in inner and outer wire-wrapped for a fast reactor annular fuel assembly - Yuefeng Guo; Yuefeng Guo; Binhang Zhang; Binhang Zhang; Xianbao Yuan; Xianbao Yuan; Xiaochao Du; Xiaochao Du; Yonghong Zhang; Yonghong Zhang; Chao Tan (Frontiers in Energy Research, 2022)
The annular fuel has dual-cooled surfaces internally and externally. Compared with traditional cylindrical fuel, the inner flow field is introduced on the annular fuel assembly, and wire-wrapped can influence the inner flow field. In order to research and compare the effect of wire-wrapped on the sub-channels and inner flow field of the fast reactor annular fuel assembly, thermal-hydraulic properties of the fast reactor annular fuel assembly with the inner and outer wire-wrapped are investigated in this research. The flow, heat transfer, and mechanical properties are analyzed, including temperature, transverse velocity, pressure drop, and thermal stress. The temperature of three sub-channels is the key that influences the temperature characteristics. The wire-wrapped reduces the coolant temperature gradient, flattens the coolant outlet temperature, and makes the coolant outlet temperature more uniform. The transverse velocity of coolant in the sub-channels is about three times that of in the inner flow field. From the perspective of the inner flow field, the increase in the number of wire-wrapped leads to an increase in transverse velocity. The number of wire-wrapped is not as good as possible from the perspective of sub-channels. The pressure drop of the sub-channels is larger than the pressure drop of the inner flow field. No matter the sub-channels or the inner flow field, the increase in the number of wire-wrapped will cause an increase in the pressure drop. The thermal-hydraulic properties of one inner and outer wire-wrapped are better than other models. The stress in the cladding is about 1.75 times the stress in the annular fuel rod, and the stress in the inner cladding is higher than that in the outer cladding. The research provides a reference for the optimization design of the fuel assembly.